Frontiers: Determining the Validity of Large Language Models for Automated Perceptual Analysis - Li, Peiyao; Castelo, Noah; Katona, Zsolt; Sarvary, Miklos (Marketing Science, 2024)
The paper explores the potential of Large Language Models to substitute for or to augment human participants in market research.